PENGARUH CITRA MEREK, KUALITAS PRODUK DAN DESAIN PRODUK TERHADAP KEPUTUSAN PEMBELIAN LUWAK WHITE COFFEE DI KOTA BATAM - Tan, Andi; Saputra, Asron (SCIENTIA JOURNAL, 2023)
Various initiatives were carried out by the company to boost product sales to meetconsumer demand. When a person recognizes a need in general and wants inparticular, the buying process occurs. The difference between the desired state andthe existing condition begins to register in the person's consciousness. Becauseeveryone has different points of reference and attitudes towards goods, one's buyingbehavior can be said to be unique. Brand Image, Product Quality and Product Designare existing factors that can influence purchasing decisions. The sampling techniqueuses simple random sampling. For data collection purposes, the researcherdistributed questionnaires, which contained a list of questions that had to beanswered by the participants. The method used in the findings contained in this studyis a quantitative-based research by conducting multiple linear analysis. The results ofresearch based on a study will certainly be able to prove that brand image, productquality and product design have a significant effect on purchasing decisions for LuwakWhite Coffee in Batam City.